NtMYB4 and NtCHS1 Are Critical Factors in the Regulation of Flavonoid Biosynthesis and Are Involved in Salinity Responsiveness - Chen, Shuai; Wu, Fengyan; Li, Yiting; Qian, Yanli; Pan, Xuhao; Li, Fengxia; Wang, Yuanying; Wu, Zhenying; Fu, Chunxiang; Lin, Hao; Yang, Aiguo (Frontiers in Plant Science, 2019)
High levels of salinity induce serious oxidative damage in plants. Flavonoids, as antioxidants, have important roles in reactive oxygen species (ROS) scavenging. In the present study, the tobacco R2R3 MYB type repressor, NtMYB4, was isolated and characterized. The expression of NtMYB4 was suppressed by salinity. Overexpression of NtMYB4 reduced the salt tolerance in transgenic tobacco plants. NtMYB4 repressed the promoter activity of NtCHS1 and negatively regulated its expression. Rutin accumulation was significantly decreased in NtMYB4 overexpressing transgenic plants and NtCHS1 RNAi silenced transgenic plants. Moreover, high H2O2 and O2− contents were detected in both types of rutin-reduced transgenic plants under high salt stress. In addition, exogenous rutin supplementation effectively scavenged ROS (H2O2 and O2−) and improved the salt tolerance of the rutin-reduced transgenic plants. In contrast, NtCHS1 overexpressing plants had increased rutin accumulation, lower H2O2 and O2− contents, and higher tolerance to salinity. These results suggested that tobacco NtMYB4 acts as a salinity response repressor and negatively regulates NtCHS1 expression, which results in the reduced flavonoid accumulation and weakened ROS-scavenging ability under salt stress.